Analisis Daya Saing Ekspor Teh Indonesia ke Pasar ASEAN Periode 2004-2013 - Satryana, Made Hardi; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 5, Mei 2016 (pp. 530-651), 2016)
Tea is one ofIndonesian main export. This study aimed to analyze the strength of competitiveness, market share and stability of Indonesian competitiveness tea export in ASEAN market. The method analyzed by Revealed Comparative Advantage (RCA) and Constant Market Share Analysis (CMSA). The comparators used are Vietnam, Malaysia, Singapore and Thailand. Calculation results show that the average value of RCA Indonesia period 2004-2013 amounted to 2,184 can be interpreted that the tea has strong competitiveness in  ASEAN market. CMSA value showsthat although Indonesian tea less attractive in ASEAN market for commodity composition effect is negative, however exports of Indonesian tea distributed to countries that import growth quickly and has strong competitiveness in ASEAN market. Results of linear trend shows that the competitiveness of Indonesian tea export to ASEAN market is unstable and tend to decline during the period 2004-2013 .
Keywords: Competitiveness , Export , Indonesian Tea , RCA , CMSA